2011
DOI: 10.1155/2011/175362
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cellulose-Hydroxyapatite Nanocomposites for Bone Regeneration

Abstract: The aim of this study was to develop and to evaluate the biological properties of bacterial cellulose-hydroxyapatite (BC-HA) nanocomposite membranes for bone regeneration. Nanocomposites were prepared from bacterial cellulose membranes sequentially incubated in solutions of CaCl2 followed by Na2HPO4. BC-HA membranes were evaluated in noncritical bone defects in rat tibiae at 1, 4, and 16 weeks. Thermogravimetric analyses showed that the amount of the mineral phase was 40%–50% of the total weight. Spectroscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
147
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(154 citation statements)
references
References 37 publications
7
147
0
Order By: Relevance
“…Nanocomposites based on nanocellulose, nano-or microfibrilliar cellulose, cellulose nanofibers are new generation nanomaterials possessing wide range of practical applications in such domains as pharmacology 1 and medicine 2 , tissue engineering [3][4][5] , biosensors 6 , microfluidics elements 7 , materials for microencapsulation 8 and drug delivery [9][10][11][12] , as permoselective membranes 13 , and as a barrier to protect mucosal tissues 14,15 . The nanoscale cellulose possesses a whole complex of unique properties typical for nanomaterials in general, such as high specific surface area, enhanced chemical reactivity, high mechanical durability, together with biocompatibility, biodegradability, and non-toxicity, which make it an excellent candidate for drug release applications.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocomposites based on nanocellulose, nano-or microfibrilliar cellulose, cellulose nanofibers are new generation nanomaterials possessing wide range of practical applications in such domains as pharmacology 1 and medicine 2 , tissue engineering [3][4][5] , biosensors 6 , microfluidics elements 7 , materials for microencapsulation 8 and drug delivery [9][10][11][12] , as permoselective membranes 13 , and as a barrier to protect mucosal tissues 14,15 . The nanoscale cellulose possesses a whole complex of unique properties typical for nanomaterials in general, such as high specific surface area, enhanced chemical reactivity, high mechanical durability, together with biocompatibility, biodegradability, and non-toxicity, which make it an excellent candidate for drug release applications.…”
Section: Introductionmentioning
confidence: 99%
“…BC has been proposed for application in tissue engineering as a scaffold for cartilage [66,67], bone repair [68][69][70][71], vascular grafts [64,[72][73][74][75] and neural repair [75][76][77][78], or as a barrier membrane for guided bone regeneration [57,58,60,70,71,79]. In addition several composite materials have been developed with the purpose of rendering BC bioactive such as hydroxyapatite (HA) [79][80][81][82][83][84][85], collagen [70,[86][87][88], gelatin [85,89], peptides [71,90] and some polymers such as chitosan [35], silk [90][91][92][93], polyhydroxybutyrate [94,95] and poly(2-hydroxyethyl methacrylate) [96].…”
Section: Scaffoldmentioning
confidence: 99%
“…The authors reported that the BC-HA membranes were effective for bone regeneration in bone defects of rat tibiae. It was found that EPN membranes accelerated new bone formation at the defect sites interestingly the reabsorption of the EPN membranes was slow enough, suggesting that this composite takes longer time to be fully reabsorbed (Saska and Barud 2011). glycerin-25 % banana fiber composite.…”
Section: Epn From Cellulosementioning
confidence: 99%